Clinical Characteristics and Outcomes of Respiratory Viral Infections in Pediatric Cancer Patients, Single center experience - Mona Mohammed; Yassin Taher; Maha Mohammed; Naiven Mohamed; Nehad Abd Elfatah; Marwa Jamal; Omnya Ahmed; Amira Sameh; Mohamed Kamal; Youssef Madney (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Respiratory viral (RV) infections cause morbidity and mortality in immunocompromised pediatric patients undergoing cancer treatment. The burden of RV infections in pediatric oncology populations from low- and middle-income countries (LMICs) remain limited. We aimed to detect the prevalence of viruses causing respiratory infections among pediatric patients with cancer and guide empiric therapy and improve patient outcomes. Methods Retrospectively we collected nasopharyngeal swabs and clinical and demographic data from pediatric patients under cancer treatment with respiratory symptoms at Children’s Cancer Hospital Egypt-57357 from September 2023 until March 2025. Samples were tested using multiplex PCR for 16 respiratory viruses. Results A total of 1710 samples were collected from 784 patients with a median age of 7 years and a male-to-female ratio of 1.26:1. Viral pathogens were detected in 1037 swabs (60.6%). The most frequently identified virus was human rhinovirus (HRV) (51.3%), followed by parainfluenza virus (PIV) (9%), respiratory syncytial virus (RSV) (8%), SARS-CoV-2 (6.4%), and human metapneumovirus (HmpV) (5.8%). Co-infections were observed in 13% of samples, commonly involving RSV, PIV, and adenovirus. The main symptoms were fever (85.7%), lower respiratory tract infection (LRTI) (59.4%), and cough (57.7%). HRV were associated with fever (p=0.01), cough (p=0.02), and hospital admission (p=0.006). PIV infection were associated with increased hospital admission (p=0.04) and need for inotropes (p=0.02), while HmpV was significantly related to LRTI (p=0.01). There was no statistically significant association between virus type and mortality (p=0.64). When correlating patient characteristics with clinical symptoms and outcomes, several significant associations were found. Lower neutrophil count (<500) correlated with rhinorrhea (p<0.001), oxygen need (p=0.01), hospital admission (p=0.001) and intensive care unit (ICU) admission (p=0.04). Female sex was significantly associated with oxygen requirement (p=0.03) and ICU admission (p=0.02); and patients with hematologic malignancies were more likely to require oxygen support (p=0.01). Conclusion RV infections are common among pediatric cancer patients presenting with respiratory symptoms, with predominance of HRV and linked to key clinical manifestations and hospital admission. Host factors such as female sex, hematology tumors, and profound neutropenia were also associated with increased illness severity and need for supportive care. However, mortality did not significantly differ among virus types, suggesting that while RV infections contribute substantially to morbidity, mortality in immunocompromised children likely depends on multifactorial host and disease-related factors.